The Australian labour market in 2018. (June 2019) - Oliver, Damian; Yu, Serena
In 2018, the Australian labour market continued to see only very moderate wages growth despite strong employment growth and low unemployment. This remains an international phenomenon with underlying economic and legal structural causes. Employment growth was concentrated in part-time jobs for both males and females, and in both manufacturing and white-collar industries. The Fair Work Commission increased the National Minimum Wage by 3.5%, a higher percentage increase than previous years but one that reflected higher growth in average earnings and inflation. The climate surrounding agreement making was less febrile than in recent years, with fewer high-profile attempts to terminate existing enterprise agreements. However, collective bargaining coverage in the private sector continues to decline to historic lows. Changes to skilled migration were the most significant shift in labour market policy in 2018, with a significant reduction in the number of permanent skilled migrants and a new temporary skilled migrant visa category with much stricter eligibility requirements. If sustained, this reduction may contribute to increasing pressure on wages in the years to come.